2013
DOI: 10.1017/s0373463313000209
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Usability of Pedestrian Navigation Interfaces by means of Landmark Visibility Analysis

Abstract: Communicating location-specific information to pedestrians is a challenging task which can be aided by user-friendly digital technologies. In this paper, landmark visibility analysis, as a means for developing more usable pedestrian navigation systems, is discussed. Using an algorithmic framework for image-based 3D analysis, this method integrates a 3D city model with identified landmarks and produces raster visibility layers for each one. This output enables an Android phone prototype application to indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…For instance, they are used in estimating the visibility of a landmark [182,183], assessing façade visibility for city marketing [184,185], in determining the optimal location for surveillance cameras [186][187][188], sensor coverage assessment [189], improving road safety [190], assessing sniper hazards [191], and in real estate mass valuation in the urban areas, based on the assumption that the view from an apartment is one of the factors driving its price [192][193][194]. Further applications involve predicting the visibility of GNSS satellites in the built environment and mitigating the multipath effect [195][196][197][198][199][200][201][202][203][204].…”
Section: Visibility Analysismentioning
confidence: 99%
“…For instance, they are used in estimating the visibility of a landmark [182,183], assessing façade visibility for city marketing [184,185], in determining the optimal location for surveillance cameras [186][187][188], sensor coverage assessment [189], improving road safety [190], assessing sniper hazards [191], and in real estate mass valuation in the urban areas, based on the assumption that the view from an apartment is one of the factors driving its price [192][193][194]. Further applications involve predicting the visibility of GNSS satellites in the built environment and mitigating the multipath effect [195][196][197][198][199][200][201][202][203][204].…”
Section: Visibility Analysismentioning
confidence: 99%
“…At different distances (4.8 m, 2.4 m and right on the end line of the corridor), the wall with the local material will be seen differently. Some studies of visibility also shown from where an object can be visible to the observer [11,12]. This study showed not only where an object can be visible by the observer, but also how visible the object is by measuring the region area using MatLab.…”
Section: Discussionmentioning
confidence: 73%
“…The ability to ignore irrelevant information may improve learning performance, but in some cases, it can deteriorate learning performance. Inattention to global environmental cues might be disadvantageous for spatial learning because global cues serve as orientation beacons (Steck & Mallot, 2000) that impose an absolute reference frame (O'keefe & Nadel, 1978), help users align spatial information, and determine the relative location of routes and landmarks in the environment (Gunzelmann & Anderson, 2006;Delikostidis et al, 2013). With these roles in mind, we defined global landmarks for the present study as peripheral and highly salient environmental cues that can be observed from a large portion of the environment and remain relatively constant in relation to the short distances travelled by the observers (Steck & Mallot, 2000).…”
Section: Attentional Narrowing and Global Landmarksmentioning
confidence: 99%